2022
DOI: 10.3390/ijms231810687
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between Ca2+ Signaling and Cancer Stemness: The Link to Cisplatin Resistance

Abstract: In the fight against cancer, therapeutic strategies using cisplatin are severely limited by the appearance of a resistant phenotype. While cisplatin is usually efficient at the beginning of the treatment, several patients endure resistance to this agent and face relapse. One of the reasons for this resistant phenotype is the emergence of a cell subpopulation known as cancer stem cells (CSCs). Due to their quiescent phenotype and self-renewal abilities, these cells have recently been recognized as a crucial fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 143 publications
0
3
0
Order By: Relevance
“…The resistance mechanism of cisplatin is very complex, and its resistance is often related to "drug pump" proteins, molecular detoxification, DNA damage repair, and activation of certain pathways (Amable, 2016). Some previous studies have begun to focus on the mechanism of cisplatin resistance and potential intervention targets (Wang et al, 2021;Kouba et al, 2022;. Here, we found that PCDH7 may be involved in cisplatin resistance in lung cancer through public database analysis (GSE21656 and GSE108214).…”
Section: Pcdh7 Affects the Immune Microenvironment And Therapy Respon...mentioning
confidence: 86%
“…The resistance mechanism of cisplatin is very complex, and its resistance is often related to "drug pump" proteins, molecular detoxification, DNA damage repair, and activation of certain pathways (Amable, 2016). Some previous studies have begun to focus on the mechanism of cisplatin resistance and potential intervention targets (Wang et al, 2021;Kouba et al, 2022;. Here, we found that PCDH7 may be involved in cisplatin resistance in lung cancer through public database analysis (GSE21656 and GSE108214).…”
Section: Pcdh7 Affects the Immune Microenvironment And Therapy Respon...mentioning
confidence: 86%
“…The resistance mechanism of cisplatin is very complex, and its resistance is often related to “drug pump” proteins, molecular detoxification, DNA damage repair, and activation of certain pathways ( Amable, 2016 ). Some previous studies have begun to focus on the mechanism of cisplatin resistance and potential intervention targets ( Wang et al, 2021 ; Kouba et al, 2022 ; Shi et al, 2022 ). Here, we found that PCDH7 may be involved in cisplatin resistance in lung cancer through public database analysis (GSE21656 and GSE108214).…”
Section: Discussionmentioning
confidence: 99%
“…Calcium ion (Ca2+) involved in the regulation of cells a variety of important life activities, intracellular stable Ca2+ concentration is the premise and the basis of maintaining behavior function, in the process of autophagy apoptosis, Ca2+ also plays an important role [23], Taiwan scholars [24] proved that 20-40 mM resveratrol induced oral cancer OC2 cells, resveratrol through PKC and PLC pathway, cause the endoplasmic reticulum release Ca2+, inducing cell apoptosis.…”
Section: Resveratrol Induces Autophagy and Apoptosis In Oral Cancer C...mentioning
confidence: 99%